1999
DOI: 10.1016/s0014-5793(99)00448-2
|View full text |Cite
|
Sign up to set email alerts
|

pADPRT‐2: a novel mammalian polymerizing(ADP‐ribosyl)transferase gene related to truncated pADPRT homologues in plants and Caenorhabditis elegans1

Abstract: Until recently, poly(ADP-ribosyl)ation was supposed to be confined only to polymerizing(ADP-ribosyl)transferase/ (ADP-ribose)polymerase (E.C. 2.4.2.30). Here, we present novel polymerizing(ADP-ribosyl)transferase homologues from mouse and man that lack all of the N-terminal DNA binding and BRCA1 C-terminus domains and will be designated polymerizing(ADP-ribosyl)transferase-2 as distinguished from the classical polymerizing(ADP-ribosyl)transferase (polymerizing(ADPribosyl)transferase-1). The murine polymerizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…The position of the initiation region was close to the most 5Ј-extending mouse and human PARP-2 cDNA originally isolated (6). This confirmed the size of the protein we described (6) as opposed to the shorter form of PARP-2 identified by Berghammer et al (23) and Johansson (9).…”
Section: Organization Of the Parp-2 Gene Vis à Vis The Protein Modules-supporting
confidence: 87%
See 1 more Smart Citation
“…The position of the initiation region was close to the most 5Ј-extending mouse and human PARP-2 cDNA originally isolated (6). This confirmed the size of the protein we described (6) as opposed to the shorter form of PARP-2 identified by Berghammer et al (23) and Johansson (9).…”
Section: Organization Of the Parp-2 Gene Vis à Vis The Protein Modules-supporting
confidence: 87%
“…No expression of the GFP reporter was noticed in the absence of the TATA sequence and when the plasmid contained only the intergenic region in addition to the intronic sequence. These results showed that the first intron did not contain any important transcriptional elements nor any other initiation sites as was suggested previously (23).…”
Section: Fig 2 Parp-2 and H1supporting
confidence: 87%
“…In support of these previous findings, in the present study, we show that in wildtype fibroblasts total PARP activation is a very early event, because the enzyme was activated within 15 min after oxidative or immunological challenge. Although PARP-1-deficient cells possess other enzymes capable of some poly(ADP-ribosylation) (13)(14)(15)(16)(17)(18), we found that the catalytic activity was maximally expressed in wild-type cells only. This suggests that, among the PARP homologous enzymes, PARP-1 is the major active enzyme to modulate poly(ADP-ribosylation) and the events leading to DNA repair.…”
Section: Discussionmentioning
confidence: 81%
“…In vitro, tankyrase catalyzes its automodification as well as the modification of the telomere-specific protein TRF1 in a DNAindependent manner. The third member of the PARP family, PARP-2, is a 62-kDa protein (6,7). It is activated by DNA strand breaks, but its function is unknown.…”
mentioning
confidence: 99%